KiPN: a visual notation for knowledge-intensive processes. (18th July 2019) - Netto, Joanne Manhães; Barboza, Tatiana; Baião, Fernanda Araujo; Santoro, Flavia Maria
Modelling knowledge-intensive processes (KiP) is not an easy task, due to their essential characteristics of being unstructured, based on social interactions, experience and intentions of the actors involved. The knowledge-intensive process ontology (KiPO) provides a structural conceptualisation for KiPs, precisely specifying all concepts and relations that are necessary to make a KiP explicit. However, KiPO does not provide a graphical notation, which is crucial for organisation managers, as well as process managers, modellers and executors. Some visual notations exist for the visual representation of KiP, but they miss at least one of these relevant features in the KiP representation. In this paper, we propose the knowledge-intensive process notation (KiPN), a notation for modelling KiP. KiPN is based on the principles of the theory of visual notations to develop the cognitive efficacy of a visual representation. The evaluation of KiPN indicates the cognitive effectiveness and perceived usefulness of KiPN.